2021
DOI: 10.1002/mrm.28671
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of IVIM biomarkers from diffusion‐weighted MRI in head and neck: Bayesian probability versus neural network

Abstract: This is an open access article under the terms of the Creative Commons Attribution NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 29 publications
4
27
1
Order By: Relevance
“…They found that both Bayesian and their neural network approach outperformed NLLS in terms of having lower within-subject coefficient of variations; however, the average IVIM parameter values were not provided. Given the improved repeatability observed by Koopman et al in muscle, 48 and reliability observed in other organs, 86 Bayesian approaches may prove useful for estimation of IVIM parameters in future investigations.…”
Section: Systematic Reviewmentioning
confidence: 92%
See 2 more Smart Citations
“…They found that both Bayesian and their neural network approach outperformed NLLS in terms of having lower within-subject coefficient of variations; however, the average IVIM parameter values were not provided. Given the improved repeatability observed by Koopman et al in muscle, 48 and reliability observed in other organs, 86 Bayesian approaches may prove useful for estimation of IVIM parameters in future investigations.…”
Section: Systematic Reviewmentioning
confidence: 92%
“…Various fitting strategies can be employed to obtain the parameters of interest, generally categorized as constrained nonlinear least squares (NLLS), Bayesian, or most recently deep learning approaches. 48 Within the constrained NLLS, all IVIM parameters can be obtained from a single step or a segmented approach can be used. Because D* is generally thought to be at least an order of magnitude greater than D, the intravascular contribution to the bi-exponential decay is negligible at high b-values.…”
Section: Ivim Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The IVIM feature extraction of the perfusion fraction (f), perfusion coefficient (D*) and diffusion coefficient (D) was performed using MATLAB R2019a software [ 17 ], after motion correction, in order to reduce artifacts.…”
Section: Methodsmentioning
confidence: 99%
“…To improve parameter map accuracy, the use of deep neural networks to model the biexponential IVIM fit has been proposed [15][16][17][18][19] . In a previous study, a physics-informed unsupervised approach that could train directly to in-vivo MRI data (IVIM-NET) 15,20 was implemented.…”
Section: Introductionmentioning
confidence: 99%